Magnetic Resonance Imaging of Enthesitis in Spondyloarthritis, Including Psoriatic Arthritis—Status and Recent Advances - Mathew, Ashish J.; Østergaard, Mikkel (Frontiers in Medicine, 2020)
Enthesitis, inflammation at the attachment sites of tendons, ligaments, fascia and joint capsules to bones plays a critical role in the pathogenesis of spondyloarthritis (SpA), including psoriatic arthritis (PsA). Magnetic resonance imaging (MRI) has aided in a better understanding of pathophysiology, early diagnosis, prognostication, therapeutic outcomes of therapeutics, and follow up of enthesitis. The concept of enthesitis as a focal insertional pathology has transformed over the past decade, with the help of MRI, to a more widespread entity involving both bone and surrounding soft tissues. The utility of MRI in the differential diagnosis of suspected enthesitis has recently been explored. With the emergence of the treat-to-target concept, and a domain-based approach in the management of SpA, objective and sensitive monitoring of response to targeted therapy becomes prudent. Properties like high sensitivity, ability to image intra-osseous pathology along with surrounding structures exemplify the utility of MRI technology. Considering the lack of a comprehensive, validated MRI score the Outcome Measures in Rheumatology (OMERACT) MRI in Arthritis Working Group, informed by a systematic literature review, developed the first international, consensus-based MRI-scoring system, combined with MRI definitions of pathologies for enthesitis in patients with spondyloarthritis (SpA) and PsA. An atlas with representative images of each grade of the scoring system was subsequently developed by the group to aid readers interested in using the heel enthesitis MRI scoring system (HEMRIS). The HEMRIS can find utility in clinical trials targeting enthesitis as the primary outcome. MRI also finds value for global assessment of the total burden of enthesitis. The concept of whole-body MRI (WBMRI), enabling visualization of entheses throughout the body using a single image is relatively new. The MRI whole-body score for inflammation in peripheral joints and entheses (MRI-WIPE) is a promising scoring system, which is undergoing further testing in clinical trials and longitudinal cohorts evaluating global measures of inflammation at entheses. This review discusses the role of MRI in diagnosis and monitoring of enthesitis in SpA and PsA, along with recent advances in the field, based on published literature.